2005
DOI: 10.1002/aqc.685
|View full text |Cite
|
Sign up to set email alerts
|

Fishing gear effects and ecology of the sea whip (Halipteris willemoesi (Cnidaria: Octocorallia: Pennatulacea)) in British Columbia, Canada: preliminary observations

Abstract: ABSTRACT1. We conducted a preliminary study of the effects of a shrimp beam trawl and prawn traps on sea whips (Halipteris willemoesi (Cnidaria: Octocorallia: Pennatulacea)) at two bays on Clio Channel, south central coast of British Columbia, Canada. Video and grabs surveys were conducted to estimate abundance and make observations on sea whips and their habitat.2. No adult sea whips were caught in six beam trawls. In 600 prawn (Pandalus platyceros) trap sets at Turnour Bay, 30 sea whips were found entangled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…However, chronic and intensive effects of bottom trawling fishing, with habitat degradation are wellknown (Pusceddu et al, 2014), and the long-term exploitation of the Adriatic basin could have homogenized and simplified Adriatic soft bottoms habitats and species composition even in offshore areas. In particular, habitats formed by slow growing and long-lived specimens such as sea pens, hydroids, or corals, have a high vulnerability to fishing and even reduced fishing effort may cause considerable damage to these species, preventing their recovery (Troffe et al, 2005;Greathead et al, 2014). Moreover, the impacts of trawl fishing gears on the seabed differ depending on the sediment compositions and on bottom trawl target species (Pranovi et al, 2001(Pranovi et al, , 2005Eigaard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic and intensive effects of bottom trawling fishing, with habitat degradation are wellknown (Pusceddu et al, 2014), and the long-term exploitation of the Adriatic basin could have homogenized and simplified Adriatic soft bottoms habitats and species composition even in offshore areas. In particular, habitats formed by slow growing and long-lived specimens such as sea pens, hydroids, or corals, have a high vulnerability to fishing and even reduced fishing effort may cause considerable damage to these species, preventing their recovery (Troffe et al, 2005;Greathead et al, 2014). Moreover, the impacts of trawl fishing gears on the seabed differ depending on the sediment compositions and on bottom trawl target species (Pranovi et al, 2001(Pranovi et al, , 2005Eigaard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…and H. willemoesi, respectively. In British Columbia, Troffe et al (2005) found densities of juvenile (3 to 7 mm) H. willemoesi as high as 145 m -2 . The structure provided by sea whips may be important for enhancing prey availability and providing cover from predators.…”
mentioning
confidence: 99%
“…Due to their formation of biogenic habitat and poor recovery after fishing disturbance (Greathead et al 2005;Troffe et al 2005;Heifetz et al 2009;Malecha & Stone 2009), sea pen concentrations are considered Vulnerable Marine Ecosystems (VMEs) (FAO 2009) in the North-west Atlantic, and the Northwest Atlantic Fisheries Organization (NAFO) has closed several areas to bottom-contact fishing gear on Flemish Cap to protect the sea pens there (NAFO 2017). In Canada, sea pen fields are considered Ecological or Biological Significant Areas (EBSAs; Kenchington 2014), as well as Significant Benthic Areas (DFO 2017) that require special management consideration.…”
Section: Introductionmentioning
confidence: 99%